2006
DOI: 10.1603/0046-225x(2006)35[1264:rmiott]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Modes in Onion Thrips (Thysanoptera: Thripidae) Populations from New York Onion Fields

Abstract: Thrips exhibit different reproductive modes including thelytoky (females produced from unfertilized eggs), arrhenotoky (males produced from unfertilized eggs and females produced from fertilized eggs) and deuterotoky (females and males produced from unfertilized eggs). We investigated patterns of reproductive modes in onion thrips, Thrips tabaci Lindeman, populations and potential effects of the bacterium Wolbachia and temperature on these modes. We also examined the possibility that male-producing T. tabaci p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…T. tabaci in onion Þelds have multiple reproductive modes in New York: thelytoky, the production of unfertilized females by females; arrhenotoky, the production of males from unfertilized eggs and females from fertilized eggs; and deuterotoky, the production of males and females by unfertilized eggs (Nault et al 2006). In general, NY populations of T. tabaci in June and July are primarily thelytokous, with very few males produced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T. tabaci in onion Þelds have multiple reproductive modes in New York: thelytoky, the production of unfertilized females by females; arrhenotoky, the production of males from unfertilized eggs and females from fertilized eggs; and deuterotoky, the production of males and females by unfertilized eggs (Nault et al 2006). In general, NY populations of T. tabaci in June and July are primarily thelytokous, with very few males produced.…”
Section: Discussionmentioning
confidence: 99%
“…In general, NY populations of T. tabaci in June and July are primarily thelytokous, with very few males produced. By August, the populations shift to primarily arrhenotokous and/or deuterotokous (Nault et al 2006). Chatzivassiliou et al (2002) showed that arrhenotokous populations of T. tabaci collected from leeks were able to transmit TSWV, while thrips from thelytokous populations collected from leek were nonvectors.…”
Section: Discussionmentioning
confidence: 99%
“…Because identiÞ-cation keys do not exist for T. tabaci larvae, thrips larvae were removed from plant samples and reared to the adult stage. Using a Þne paintbrush, up to 30 larvae per composite weed sample were transferred to ventilated petri dishes containing sterilized leaf disks of cabbage, Brassica oleracea L. (Capitata group), and reared to adulthood following the procedure described in Nault et al (2006). Based on experience rearing T. tabaci larvae, those larvae that were clearly not T. tabaci were not collected nor counted.…”
Section: Methodsmentioning
confidence: 99%
“…It is haplodiploid and arrhenotokous like most Thripidae, which implies that haploid, unfertilised eggs become males and diploid, fertilised eggs females. However, thelytoky (unfertilised diploid eggs, becoming females) was found in some T. tabaci populations (Murai 1990; Nault et al 2006; Zawirska 1976). …”
Section: Introductionmentioning
confidence: 99%